Doubly Metathetic NiCl2-Catalyzed Coupling Between Bis(2-oxazolines) and Aldehydes: A Novel Access to Bis(ester-imine) Derivatives - Sara Colombo; Julie Oble; Giovanni Poli; Leonardo Lo Presti; Giovanni Macetti; Alessandro Contini; Gianluigi Broggini; Marta Papis; Camilla Loro (Molecules)
The coupling between bis(2-oxazolines) and two equivalents of aromatic aldehydes in the presence of catalytic amounts of NiCl2 affords an ester-imine product in synthetically useful yields. This virtually unknown, 100% atom-economic transformation involves the formal metathesis between the C=N double bond of the bis(2-oxazoline) moiety, which undergoes ring-opening, and the C=O double bond of the aldehyde. The scope of this transformation is studied, and a mechanism is proposed based on DFT calculations.